2022
DOI: 10.3390/ijms23137421
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Storage Temperature on Indica-Japonica Hybrid Rice Metabolites, Analyzed Using Liquid Chromatography and Mass Spectrometry

Abstract: The Yongyou series of indica-japonica hybrid rice has excellent production potential and storage performance. However, little is known about the underlying mechanism of its storage resistance. In this study, Yongyou 1540 rice (Oryza sativa cv. yongyou 1540) was stored at different temperatures, and the storability was validated though measuring nutritional components and apparent change. In addition, a broad-targeted metabolomic approach coupled with liquid chromatography-mass spectrometry was applied to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…4-aminobutyric acid (GABA) can improve the resistance of rice seeds to unfavorable storage environment and delay the aging process of seeds ( Zhu et al, 2022 ). It was also reported that GABA may accumulated under adverse environments ( Chang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…4-aminobutyric acid (GABA) can improve the resistance of rice seeds to unfavorable storage environment and delay the aging process of seeds ( Zhu et al, 2022 ). It was also reported that GABA may accumulated under adverse environments ( Chang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This Special Issue aims to provide a forum on the most recent advances in the application of molecular tools to understand the mechanism for improving any cereals’ grain quality. A total of 13 papers were collected for this Special Issue [ 1 , 2 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ], mainly covering rice and wheat crops.…”
mentioning
confidence: 99%
“…The storage of rice is also an important part of its production and transactions, and only with good storage performance can its commercial value be maintained in commodity transactions. Zhu et al [ 12 ] found that under high-temperature storage conditions (35 °C), the indica–japonica hybrid rice Yongyou 1540 was not significantly worse in terms of fatty acid value, whiteness value, and changes in electron microscope profile. Metabolomics analysis identified 19 key differential metabolites, in which the lipid metabolites related to palmitoleic acid were found to affect the aging of rice.…”
mentioning
confidence: 99%